The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 1999 Symposium on Interactive 3D Graphics 1999
DOI: 10.1145/300523.300542
|View full text |Cite
|
Sign up to set email alerts
|

Using transparent props for interaction with the virtual table

Abstract: The Virtual Table presents stereoscopic graphics to a user in a workbench-like setting. This paper reports on a user interface and new interaction techniques for the Virtual Table based on transparent props-a tracked hand-held pen and a pad. These props, but in particular the pad, are augmented with 3D graphics from the Virtual Table's display. This configuration creates a very powerful and flexible interface for two-handed interaction that can be applied to other back-projected stereographic displays as well:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 22 publications
0
58
0
1
Order By: Relevance
“…As we noted in our design-space exploration in chapter 2, one strategy for mitigating the drawbacks of intangible interfaces is the provision of palette-like objects for use in virtual settings [82,183,199]. Another influential technique, introduced by Billinghurst et al [24], uses fiducial makers to act as both tracking support and proxy objects for virtual counterparts.…”
Section: Tangible Interactionmentioning
confidence: 99%
“…As we noted in our design-space exploration in chapter 2, one strategy for mitigating the drawbacks of intangible interfaces is the provision of palette-like objects for use in virtual settings [82,183,199]. Another influential technique, introduced by Billinghurst et al [24], uses fiducial makers to act as both tracking support and proxy objects for virtual counterparts.…”
Section: Tangible Interactionmentioning
confidence: 99%
“…For example, Schmalstieg et al [69] suggested to use transparent props, yet these are static and would not work well with 3D data space manipulations and time-dependent data. Hachet et al [31] separated the touch surface from the stereoscopic display in their Toucheo system, but thus significantly restricted the space in which people can interact.…”
Section: D Stereoscopic Viewing Of 3d Data Visualizationsmentioning
confidence: 99%
“…This gesture is particularly well-suited to touch-screen based interactions. For instance, Schmalstieg et al used the circling metaphor to select objects in a virtual world [28]. As for the straight strokes, heuristics are here used to recognize circular sketches, based on the shape of the stroke and the distance between the first and the last point of the sketch.…”
Section: Human Robot Interactionmentioning
confidence: 99%